Severe iron intoxication treated with exchange transfusion. Issue 4 (20th March 2008) - Carlsson, M; Cortes, D; Jepsen, S; Kanstrup, T
Abstract : An 18-month-old previous healthy girl who had ingested 442 mg elemental iron/kg was admitted to a paediatric intensive care unit. The child was treated with gastric lavage, whole bowel irrigation and intravenous deferoxamine. After 2 h of standard therapy serum iron had risen threefold to 1362 μg/dl (244 μmol/l). The child was treated with exchange transfusion (ET; 52 ml/kg) and serum iron fell to 134 μg/dl (24 μmol/l). The patient made an uncomplicated recovery. ET should be considered in severe iron poisoning when standard therapy is inadequate.